Effects of noise and music on situation awareness, anxiety, and the mental workload of nurses during operations. (February 2022) - Tseng, Li-Ping; Chuang, Mao-Te; Liu, Yung-Ching
Abstract: This study aims to explore the effects of noise and music types on nurses' anxiety, mental workload and situation awareness during an operation. Participants included 20 circulating nurses (CNs) and 16 nurse anesthetists (NAs) who completed a total of 70 operations in which each operation required one CN and one NA. The experiment was separated into a control group (operating noise only) vs. an experimental group (3 different music types-between subjects and 2 music volume levels-within-subjects). Results showed that all participants had excellent situation awareness performance despite their mental workload showing significant differences in various phases of the surgery. Music at 55–60 dB caused lower mental workloads and anxiousness for nurses than those exposed to levels of 75–80 dB. When Mozart's music was played, the participants' mental workload and situation anxiety were lower than when exposed to other music types. Music played at 60 dB during an operation may be a feasible solution to mitigate the negative effects of extra noise and thus improve the nurses' performance. Highlights: Noise exposure and music impact the effectiveness of the operation and patient safety. Sound level exhibited a significant effect on the mental workload and anxiety of nurses. The nurses' SWAT scores and STAI-S scores were positively correlated. However, the nurses' SA remained unaffected and kept in excellent levels. Mozart music set at 60 dB during the operation could improve the nurses' performance.